Original paperInfluence of azelaic and mandelic acid peels on sebum secretion in ageing women - Wójcik, Aneta; Kubiak, Marlena; Rotsztejn, Helena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: Azelaic acid and mandelic acid are superficial peels commonly applied in people of various age groups. As they are mild and do not cause any side effects, they are also often used in elderly people. Aim : To compare the influence of azelaic and mandelic acid peels on facial sebum secretion in mature women aged 49-71 years. Material and methods: The level of secreted sebum was measured in 28 women. Eleven women were treated with azelaic acid peel and 17 with mandelic acid peel. Each of the peels was applied five times with 2-week intervals. The measurements were made on the cheeks and chin with the use of Sebumeter SM 15 (Courage & Khazaka, Germany). The last measurement, i.e. the sixth one, was made 2 weeks after the treatment. Results : We observed a significant increase in sebum secretion in the U-zone after the application of 20% azelaic peel and 40% mandelic peel. Neither peel significantly affected sebum secretion in the T-zone. Conclusions : Peels with 20% azelaic acid and 40% mandelic acid might be considered treatments which contribute to an increase in sebum secretion in ageing women.